2008
DOI: 10.1007/s10265-008-0198-0
|View full text |Cite
|
Sign up to set email alerts
|

Growth strategies differentiate the spatial patterns of 11 dipterocarp species coexisting in a Malaysian tropical rain forest

Abstract: We examined relationships between mortality rate, relative growth rate (RGR), and spatial patterns of three growth stages (small, medium, and large trees) for 11 dipterocarp species in the Pasoh 50-ha plot. Mortality rates for these species tended to be positively correlated with RGRs, although the correlation was significant only at the small-tree stage. Seven species with high growth and mortality rates exhibited peaks in spatial aggregation at small distances (<100 m) in small trees, but this aggregation di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 52 publications
0
21
0
1
Order By: Relevance
“…Dipterocarp species have been shown to have habitat associations with both topography and edaphic factors in a number of studies (Paoli et al 2006;Russo et al 2008;Suzuki et al 2009). Paoli et al (2006) showed that 18 of 22 species of dipterocarp at a site in Borneo showed negative or positive associations with either granitic or alluvial soils, similar observations were also made with soil nutrients.…”
Section: Restoration Of Degraded Landsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dipterocarp species have been shown to have habitat associations with both topography and edaphic factors in a number of studies (Paoli et al 2006;Russo et al 2008;Suzuki et al 2009). Paoli et al (2006) showed that 18 of 22 species of dipterocarp at a site in Borneo showed negative or positive associations with either granitic or alluvial soils, similar observations were also made with soil nutrients.…”
Section: Restoration Of Degraded Landsmentioning
confidence: 99%
“…These associations are thought to reflect trade-offs between fast growth and low mortality (Russo et al 2008). In a study of eleven species of dipterocarp at a site in Peninsular Malaysia, Shorea maxwelliana was associated with well-drained alluvial soils on flat lands, while S. leprosula favoured less well-drained valley soils (Suzuki et al 2009). Many of these habitat associations were significant at early life stages, emphasising the importance of these factors for site-species matching in the early establishment phase of forest restoration.…”
Section: Restoration Of Degraded Landsmentioning
confidence: 99%
“…At the community level, univariate spatial patterns (aggregation/regularity) of fruiting trees were analyzed using Ripley's K(t) function for all individuals ([30 cm in DBH) (see Suzuki et al 2009). Species-specific spatial patterns were analyzed for the 12 species with sufficient number of samples (n [ 20).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that rainforest tree species can be classified into several types of guilds, strategies or functional groups (e.g., climax and pioneer species in Whitmore and Burnham 1984). Suzuki et al (2009) examined growth strategies of 11 dipterocarp species in the 50-ha plot of the Pasoh Forest Reserve, and classified the species into fast-growing species with high mortality rates and slow-growing with low mortality rates. Six species (S. acuminata, S. lepidota, S. leprosula, S. ovalis, S. parvifolia, and S. pauciflora) in our study were regarded as fastgrowing.…”
Section: Factors Affecting Fruiting Behaviormentioning
confidence: 99%
“…种 间 关 系 是 植 物 群 落 重 要 的 数 量 特 性 之 一 (Connell, l983;Schoener, 1983;Bruno et al, 2003;张金屯, 2004 (Cox, 1979;Suzuki et al, 2012), 并能为森林经营管理和生物多样性保护等 提供理论依据 (Rao et al, 1997;Rosenthal, 2003;张 金屯和焦蓉, 2003;Thevathasan & Gordon, 2004), 因 而具有重要的生态学意义。 确定种间关系的主要方法包括种间联结和种 间相关的测定。种间联结以二元数据为基础 (Forbes, 1907;Hurlbert, 1969;杜道林等, 1995;周先叶等, 2000), 定性地检验两个物种是否存在关联; 而种间 相关以物种的数量数据为基础, 是一个定量测度 (Legendre & Legendre, 1983; 杨兆静等, 2013)。在以 往的研究中, 种间关系常常与其他生态学问题结合 在一起研究, 如种间关系与群落结构 (Hale, 1955;Bray, 1956;Greig-Smith, 1957;Kershaw, 1960;郑超 超, 2014), 种间关系与生态种组 (Mueller-Dombois & Ellenberg, 1986;Li et al, 2008;Suzuki et al, 2009;Su et al, 2015), 种间关系与竞争 (Grim, 1979;Tilman, 1988;Bertnes & Hacker, 1994;Cheng et al, 2006), 种间关系与演替 (杜道林等, 1995 …”
unclassified